DEVELOPMENT OF EFINACONAZOLE NAIL GEL FOR THE TREATMENT OF ONCHOMYCOSIS - SUNDARI, IVATURI BALA TRIPURA; KALVA, SIREESHA; BINDU, MALAVIKA (International Journal of Current Pharmaceutical Research, 2023)
Objective: The present research has been undertaken with the aim to develop a topical nail gel formulation of Efinaconazole. Efinaconazole is considered highly desirable to treat common nail disorders such as Onychomycosis due to localized effects and improved adherence. Efinaconazole topical gel preparations are not yet available in the market thus, this formulation is made for better patient compliance. Efinaconazole nail gel is formulated with unique ingredients added to an alcohol-based formulation to provide low surface tension and good wetting properties. Methods: The nail gels were formulated by using different gelling agents. Various formulations [F1-F10] were developed using a suitable polymer [Carbopol-934, Xanthan gum, CMC]. The formulations were evaluated for pH, viscosity, spreadability, % Drug content, extrudability, stability testing, in vitro drug diffusion studies, and in vitro antifungal activity. Results: The results showed that Efinaconazole nail gel had good antifungal activity. Viscosity studies and pH studies revealed that formulation F2 was better when compared to other formulations. Results indicate that the 0.75% concentration of carbopol-934 is the ideal among other formulations. Conclusion: It was concluded that formulation F2, containing a 0.75% concentration of Carbopol-934 was the best formulation of all.